A Pilot Study of Home-Based Exercise and Personalized Nutrition Counseling Intervention in Endometrial Cancer Survivors - Schwartz, Amanda R.; Bartlett, David B.; Johnson, Johanna L.; Broadwater, Gloria; Channell, Meghan; Nolte, Kimberly C.; Wilkes, Patricia A.; Huffman, Kim M.; Secord, Angeles Alvarez (Frontiers in Oncology, 2021)
Introduction: To assess the feasibility of a home-based aerobic exercise and nutrition counseling intervention and effect on cardiorespiratory fitness, cardiovascular disease risk profile, and immune response in obese endometrial cancer survivors. Methods: A longitudinal pilot study assessed a 12-week home-based aerobic exercise and nutrition counseling intervention in obese endometrial cancer survivors. The primary outcome was feasibility defined as 80% adherence to weekly walking sessions calculated among individuals that completed the intervention. Secondary outcomes comprised pre- and post-intervention differences in cardiorespiratory fitness, cardiovascular risk factors, and T-cell function. Descriptive statistics summarized data. Wilcoxon sign tests identified differences between and pre and post-intervention variables. Results: Nineteen women with stage 1 endometrial cancer consented; 9 withdrew and one was a screen failure. Median adherence to weekly walking sessions was 83.3%. Body composition was significantly altered with a reduction in median fat mass from 52.5 kg to 46.9 kg (p=0.04), and BMI from 37.5 kg/m2 to 36.2 kg/m2 (p = 0.004). There was no significant difference in cardiorespiratory fitness or cardiovascular parameters. The percentage of CD4+ and CD8+ T-cells producing IFNγ towards MAGE-A4 significantly increased from and 5.9% to 7.2% (p=0.043) and 13.9% to 14.8% (p=0.046), respectively. There were 3 related adverse events: hip pain, back sprain, and abdominal pain. Discussion: Our home-based exercise and nutrition counseling program was feasible based on 80% adherence to walking sessions and favored altered body composition. However, the discontinuation rate was high and further research is needed to overcome barriers to implementation. Improvement in cardiovascular parameters will most likely require longer and more intensive programs.